DIRECT MEASUREMENT OF 44CA/40CA RATIOS BY MC-ICP-MS USING THE COOL PLASMA TECHNIQUE - Fietzke J.; Eisenhauer A.; Gussone N.; Bock B.; Liebetrau V.; Dullo C.; Nägler T.F.; Spero H.J.; Bijma J. (My University, 2004)
Here, we present a new technique for the direct measurement of Ca/Ca isotope ratios on a Multicollector Inductively Coupled Plasma Mass Spectrometer (MC–ICP–MS, AXIOM) using the ‘‘cool plasma’’ technique. By reducing the plasma energy to about 400W, the isobaric effect resulting from Ar can be significantly reduced, enabling the simultaneous and precise measurement of Ca and Ca beam intensities in different Faraday cups. In contrast to the TIMS technique requiring a Ca/Ca double spike, the isotope measurements on MC–ICP–MS can be performed by bracketing standards. We express the calcium isotope variation relative to NIST SRM 915a (dCa [x]=[((Ca/Ca)sample/( Ca/Ca)NIST SRM 915a) 1]*1000). Isobaric effects of MgO and NaOH interfering with Ca and MgOH2 + with Ca can be neglected by measuring calcium isotopes near the low-mass edge of the peaks. No influence of Sr + monitored on 43.5 atomic mass units (amu) was found. Repeatedmeasurements of two JohnsonMatthey CaCO3 standards (lot No. 4064 and lot No. 9912) revealed values of about 11.29 (x SRM 915a) and 0.57 (x SRM 915a). These values are in accordance with previous values published by Russell et al. [Geochim. Cosmochim. Acta 42 (1978) 1075], Heuser et al. [Int. J. Mass Spectrom. 220 (2002) 385], Hippler et al. [Geostand. Newsl. 27 (2003) 267] and Schmitt et al. [Geochim. Cosmochim. Acta 67 (2003) 2607]. Repeated measurement of the NIST SRM 915a CaCO3 standard showed that the variance of a single d Ca measurement is about 0.14x RSD being comparable with TIMS. MC–ICP–MS-based dCa values measured on inorganically precipitated aragonite samples are indistinguishable from earlier measurements based on TIMS, confirming the positive correlation of dCa and temperature. MC–ICP–MS-based dCameasurements on culturedOrbulina universa showed a slope of about 0.026x/jCbeing similar to the TIMS-based dCa measurements showing a slope of about 0.019x/jC. The large offset of about 5x between the two techniques is shown to be caused by a ‘‘matrix’’ effect, indicating that any dCa measurements on MC–ICP–MS are sensitively controlled by the Ca concentration and the acidity of the solution. Our study demonstrates the possibility to measure the whole dispersion of calcium isotopes with MC–ICP–MS, showing that Ca can be used for normalization of Ca. D 2004 Elsevier B.V. All rights reserved.
Keywords: Calcium isotopes; MC–ICP–MS; Cool plasma; Fractionation